Keutamaan kriteria pengurusan risiko dalam rantaian bekalan kilang kelapa sawit: pendekatan AHP - Darwinah, Mohd Darwin Lim (2016)
This study describes the seven components of the inherent risks that exist along the Palm Oil Plant (KMKS) supply chains, which are the Demand Risk (RP), Inventory Risk (RI), Supply Risk (RB), Environmental Risk (RS), Transportation Risk (RA), Delay Risk (RK) and Manpower Risk (RT), in which each has its own elements. 21 units of KMKS in Lahad Datu, Sabah, were selected to participate in this study. The Palm Oil Industry (IMKS) was chosen because it is the major contributor to KDNK. Most past research concerning IMKS focused on competitiveness, sustainability and obstacles in production. However, there is very little study that focused on the main risks which require more attention in the KMKS supply chain management. Face to face interviews were conducted in the early stages to get information about the risks in the supply chain of the plant. It was then followed by the distribution of questionnaires to obtain more detailed data for analysis purposes. This study applied the Saaty method called Analytical Hierarchy Process (AHP) for measuring the risk weighting components. In addition, the use of AHP was also referred to as an indicator of the level of interest risk in the KMKS supply chain. The analysis shows that KMKS should give priority to the RP component because this risk has the highest value compared to other risks. This is followed by RI, RB, RS, RT, RA and lastly RK. Overall, this study will help the plant in identifying the most important risk that needs to be addressed in advance to avoid any problems along the KMKS supply chain process.